Recycling method of graphite in waste negative electrode, graphite negative electrode material, secondary battery and electric equipment
Through inert calcination, high-temperature secondary calcination of air, acid leaching treatment and vapor deposition technologies, the problems of defects and impurities in waste graphite are solved, efficient decomposition and regeneration of graphite are achieved, electrochemical performance and cycle stability are improved, and carbon reduction goals are achieved.
Patent Information
- Application Number
- CN202510059101.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art is difficult to effectively remove defects and impurities in waste graphite, resulting in low graphite recycling and reuse efficiency.
Through inert calcination, air high-temperature secondary calcination, acid leaching treatment and vapor deposition technology, defects and impurities on the surface of graphite are repaired and the purity and performance of graphite are improved.
It has achieved efficient decomposition and regeneration of waste graphite, improved the electrochemical performance and cycle stability of graphite, reduced production energy consumption, and achieved the carbon reduction goal.
Smart Images

Figure BDA0005244085620000111 
Figure BDA0005244085620000131
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a method for recovering graphite from waste negative electrodes, a graphite negative electrode material, a secondary battery and an electrical device. Background Art
[0002] The average service life of power batteries for new energy vehicles is about 6 to 8 years. Power batteries will usher in a large-scale retirement wave in the next 1-2 years, so there is a large room for development in the recycling of waste batteries. As one of the main components of waste batteries, waste graphite negative electrodes account for a large proportion of the recycling volume in the entire battery recycling market. The production process of normal negative electrode graphite includes the production of raw coke, crushing and grinding, graphitization process and other processes, which takes more than 20 days in total, and the graphitization temperature is as high as about 2800℃. This process is not only time-consuming but also energy-intensive; the recycling and reuse of waste negative electrode graphite is conducive to reducing the cost of negative electrode materials, and will also greatly reduce production energy consumption and achieve carbon reduction goals. However, the graphite stripped from the waste negative electrode sheet generally has many internal defects, more impurities, lattice structure damage, and larger interlayer spacing. It needs to be repaired through complex impurity removal and regeneration processes.
[0003] Therefore, it is necessary to develop a simple and effective method for removing impurities and regenerating waste graphite. Summary of the invention
[0004] The purpose of this application is to overcome the above-mentioned defects in the prior art and provide a simple and effective method for recycling waste graphite.
[0005] To achieve the above object, the first aspect of the present application provides a method for recovering graphite from waste negative electrodes, comprising the following steps:
[0006] S1 secondary battery is discharged and disassembled to obtain waste negative electrode plates;
[0007] S2: the waste negative electrode sheet obtained by disassembling in step S1 is placed in an inert atmosphere for calcination to obtain a black powder;
[0008] S3: the black powder obtained in step S2 is placed in an air atmosphere for secondary calcination, and then subjected to acid leaching, washing and drying to obtain waste graphite;
[0009] S4: The waste graphite obtained in step S3 is calcined under the conditions of a carbon source and an inert atmosphere, and a carbon layer is vapor-deposited on the surface of the waste graphite to obtain regenerated graphite.
[0010] As an embodiment of the present application, the primary calcination in step S2 is performed at a temperature of 300-500° C. and for a time of 0.5-3 h.
[0011] As an embodiment of the present application, the calcination procedure of the primary calcination in step S2 is: firstly heating the temperature to 350-400°C at a heating rate of 5-10°C / min, and then heating the temperature to 500°C at a heating rate of 1-4°C / min.
[0012] As an embodiment of the present application, the temperature of the secondary calcination in step S3 is 500-700°C, the time is 0.5-1h, and the heating rate is 5-10°C / min.
[0013] As an embodiment of the present application, the acid used for pickling in step S3 includes at least one of hydrochloric acid, nitric acid, sulfuric acid, citric acid, boric acid, acetic acid, acetic acid, gluconic acid, and oxalic acid.
[0014] As an embodiment of the present application, in the acid leaching process described in step S3, the ratio of black powder to acid is 1g: 0.0003-0.005mol.
[0015] As an embodiment of the present application, in the acid leaching described in step S3, the acid concentration is 0.1-0.5 mol / L.
[0016] As an embodiment of the present application, the acid leaching temperature in step S3 is 40-80° C., and the immersion time is 1-3 hours.
[0017] As an embodiment of the present application, the carbon source in step S4 includes at least one of acetylene, methane, ethylene, propane, toluene, cyclohexane, ethanol, ethylene, propylene, pyrrole, and acetonitrile.
[0018] As an implementation method of the present application, the carbon source in step S4 is introduced at a flow rate of 10 to 400 mL / min.
[0019] As an embodiment of the present application, the calcination temperature in step S4 is 800-1200° C., the time is 10-60 min, and the heating rate is 5-10° C. / min.
[0020] As an embodiment of the present application, the gas forming the inert atmosphere includes at least one of helium, argon, and nitrogen.
[0021] The second aspect of the present application provides a graphite negative electrode material, which is prepared by the method for recovering graphite from waste negative electrodes described in the first aspect of the present application.
[0022] According to a third aspect of the present application, a secondary battery is provided, comprising a positive electrode plate, an electrolyte, a separator and a negative electrode plate, wherein the negative electrode plate comprises a negative electrode collector and a negative electrode active material layer arranged on at least one surface of the negative electrode collector, wherein the negative electrode active material layer comprises the graphite negative electrode material described in the second aspect of the present application.
[0023] In a fourth aspect of the present application, an electrical device is provided, wherein the electrical device comprises the secondary battery described in the third aspect of the present application.
[0024] Compared with the prior art, the beneficial effects of this application are:
[0025] This application uses recycled graphite powder as raw material, and after "inert calcination + high-temperature secondary calcination in air", it is acid-leached, and finally a carbon layer is deposited on the surface of the purified recycled graphite through vapor deposition technology to repair the defects of the graphite surface. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0027] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0028] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0029] The reagents or instruments used in this application without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.
[0030] In a first aspect of the present application, a method for recovering graphite from waste negative electrodes is provided, comprising the following steps:
[0031] S1 secondary battery is discharged and disassembled to obtain waste negative electrode plates;
[0032] S2: the waste negative electrode sheet obtained by disassembling in step S1 is placed in an inert atmosphere for calcination to obtain a black powder;
[0033] S3: the black powder obtained in step S2 is placed in an air atmosphere for secondary calcination, and then subjected to acid leaching, washing and drying to obtain waste graphite;
[0034] S4: The waste graphite obtained in step S3 is calcined under the conditions of a carbon source and an inert atmosphere, and a carbon layer is vapor-deposited on the surface of the waste graphite to obtain regenerated graphite.
[0035] This application uses recycled graphite powder as raw material, and after "inert calcination + high-temperature secondary calcination in air", it is acid-leached, and finally a carbon layer is deposited on the surface of the purified recycled graphite through vapor deposition technology to repair the defects of the graphite surface.
[0036] The purpose of the first step of calcination under an inert gas atmosphere is to promote the decomposition of the binder in the waste negative electrode sheet, and to remove impurities while facilitating the fall of waste graphite black powder from the surface of the current collector and forming homogenized black powder particles. At this time, metal impurities (such as copper foil) of the current collector still exist in the waste black powder; although metal impurities can be further removed by acid leaching, if metal impurities are to be completely removed, higher acid concentrations and ultrasonic assistance are required. Higher acid concentrations will reduce the stacking height (Lc) of graphite and the number of stacked carbon planes, degrade the carbon lattice, attack the surface and interlayer structure of the graphene sheet, and form defects, especially forming "bubble" protrusions on the surface of the graphite layer, which in turn affects the bonding strength with the carbon coating layer, and affects the ion conductivity and cycle life of the battery prepared therefrom.
[0037] The inventors of the present application creatively discovered that after the first step of inert calcination, the second calcination is immediately transferred to the air to oxidize the residual copper foil in the black powder into copper oxide, which is not only beneficial for the subsequent acid immersion to remove copper impurities; at the same time, the metal will have a certain impact on the crystal structure of the graphite during the oxidation process, the interlayer spacing will increase, and the metal oxide will form micropores on the graphite surface after being removed by acid immersion. These micropores are beneficial to buffering the volume change during the lithium insertion and extraction process, increasing the lithium insertion and extraction capacity of the graphite negative electrode, and improving its electrochemical cycle performance; it is also beneficial to improve the interfacial bonding force with the carbon deposition layer, and significantly improve the electrochemical cycle stability.
[0038] The powder after acid purification (acid leaching) is decomposed into C atoms and H atoms at high temperature using a carbon source. Under the induction of graphite surface defects, carbon atoms aggregate and deposit on the surface of the purified graphite. The deposited carbon layer fills the surface defects of the waste graphite and is evenly coated on the surface of the acid-purified graphite. The anisotropic deposited carbon layer reduces the surface defects of the acid-purified graphite and also provides a fast lithium ion migration channel.
[0039] As an embodiment of the present application, the temperature of the primary calcination in step S2 is 300-500°C, and the time is 0.5-3h. The temperature of the primary calcination can be any one of 300°C, 350°C, and 500°C, or an interval formed by any two values. The time of the primary calcination can be any one of 0.5h, 1h, and 3h, or an interval formed by any two values.
[0040] In an embodiment of the present application, the calcination procedure of the primary calcination described in step S2 is: first, the temperature is increased to 350-400°C at a heating rate of 5-10°C / min, and then the temperature is increased to 500°C at a heating rate of 1-4°C / min. First, the temperature is increased to above 350°C at a faster rate, and the binder undergoes a rapid degradation reaction. There will be gas by-products during the degradation process. The impact pressure formed by the gas by-products will change or even destroy the microstructure of the graphite, thereby affecting the electrochemical properties of the battery, especially the rate performance. Therefore, the heating rate is slowed down in the later stage to facilitate the stable degradation of the binder. The heating rate can significantly improve the rate performance and cycle stability of the prepared battery within the above-mentioned appropriate range of the present application.
[0041] In an embodiment of the present application, the temperature of the secondary calcination in step S3 is 500-700°C, the time is 0.5-1h, and the heating rate is 5-10°C / min. The temperature of the secondary calcination can be any one of 500°C, 550°C, 600°C, and 700°C, or an interval formed by any two values. The time of the secondary calcination can be any one of 0.5h, 0.6h, and 1h, or an interval formed by any two values. The heating rate of the secondary calcination can be any one of 5°C / min, 6°C / min, and 10°C / min, or an interval formed by any two values. The parameters of the secondary calcination are within the above-mentioned appropriate range, which can further improve the cycle stability of the prepared battery.
[0042] In an embodiment of the present application, the acid used for acid leaching in step S3 includes at least one of hydrochloric acid, nitric acid, sulfuric acid, citric acid, boric acid, acetic acid, acetic acid, gluconic acid, and oxalic acid.
[0043] In an embodiment of the present application, in the acid leaching process described in step S3, the ratio of black powder to acid is 1 g: 0.0003-0.005 mol.
[0044] In the embodiment of the present application, the acid leaching in step S3 has an acid concentration of 0.1-0.5 mol / L. In the present application, a lower concentration of acid can be used for purification, which is beneficial to reduce costs and the treatment of waste acid solution, and is relatively environmentally friendly.
[0045] In an embodiment of the present application, the acid leaching temperature in step S3 is 40-80° C., and the immersion time is 1-3 h.
[0046] In the embodiment of the present application, the carbon source in step S4 includes at least one of acetylene, methane, ethylene, propane, toluene, cyclohexane, ethanol, ethylene, propylene, pyrrole, and acetonitrile. Common carbon sources for vapor deposition in the art can be used in the present application.
[0047] In an embodiment of the present application, the carbon source in step S4 is introduced at a flow rate of 10 to 400 mL / min.
[0048] In the embodiment of the present application, the calcination temperature in step S4 is 800-1200° C., the time is 10-60 min, and the heating rate is 5-10° C. / min.
[0049] In an embodiment of the present application, the gas forming the inert atmosphere includes at least one of helium, argon, and nitrogen.
[0050] The second aspect of the present application provides a graphite negative electrode material, which is prepared by the method for recovering graphite from waste negative electrodes described in the first aspect of the present application.
[0051] According to a third aspect of the present application, a secondary battery is provided, comprising a positive electrode plate, an electrolyte, a separator and a negative electrode plate, wherein the negative electrode plate comprises a negative electrode collector and a negative electrode active material layer arranged on at least one surface of the negative electrode collector, wherein the negative electrode active material layer comprises the graphite negative electrode material described in the second aspect of the present application.
[0052] In some embodiments, the positive electrode sheet in the secondary battery includes a positive current collector and a positive active layer disposed on at least one surface of the positive current collector, wherein the positive active layer includes a positive active material. The present application does not limit the type of positive active material, and the commonly used positive active materials in the art can be used to prepare a secondary battery in the present application. The positive active material includes but is not limited to at least one of lithium cobalt oxide, lithium iron phosphate, lithium iron manganese phosphate, and lithium nickel cobalt manganese oxide (NCM).
[0053] In the present application, there is no limitation on the types of positive electrode current collector, negative electrode current collector, separator and electrolyte, which can be selected according to the requirements. Common current collector materials, separators and electrolytes in the art can be used in the present application.
[0054] In some embodiments, the negative electrode current collector may preferably be made of copper foil or carbon-coated copper foil.
[0055] The positive electrode current collector may be made of metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, etc.; carbon materials such as carbon cloth, carbon paper, etc.; a composite material formed by a polymer and a metal layer. In some embodiments, the positive electrode current collector is preferably made of aluminum foil.
[0056] In some embodiments, the type of solvent used to form the positive electrode slurry and / or the negative electrode slurry is not limited, as long as it is a solvent that can dissolve or disperse the positive electrode active material, the negative electrode active material, the conductive agent, the binder, and the dispersant.
[0057] In the secondary battery described in the present application, the type of the separator is not particularly limited and can be selected according to actual needs. The separator can be a polypropylene film, a polyethylene film, a polyvinylidene fluoride, a spandex film, an aramid film, or a multilayer composite film modified by a coating.
[0058] In some embodiments, the preparation of a secondary battery includes: stacking the positive electrode sheet, the separator, and the negative electrode sheet in order, placing the separator between the positive and negative electrode sheets to play an isolating role, and then winding them into a square bare cell, loading them into a battery casing, and then baking them at 65 to 95°C to remove water, injecting electrolyte, sealing, and obtaining a secondary battery after standing, hot and cold pressing, formation, clamping, capacity division and other processes.
[0059] In some embodiments, the secondary battery may include an outer package, which may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the secondary battery may also be a soft package, such as a bag-type soft package, and the material of the soft package may be plastic, such as one or more of polypropylene, polybutylene terephthalate, polybutylene succinate, etc. There is no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.
[0060] In the fourth aspect of the present application, an electric device is provided, wherein the electric device includes the secondary battery described in the third aspect of the present application. The electric device may be an application device such as a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy, and an electric tool. The vehicle may be a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle, or an extended-range vehicle, etc.; the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.; the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc.; the electric tool may include a metal cutting electric tool, a grinding electric tool, an assembly electric tool, and an electric tool for railways, such as an electric drill, an electric grinder, an electric wrench, an electric screwdriver, an electric hammer, an impact drill, a concrete vibrator, and an electric planer, etc. The embodiments of the present application do not impose any special restrictions on the above-mentioned devices.
[0061] The following are specific embodiments of the present application, and the technical scheme of the present application is further described in conjunction with the embodiments, but the present application is not limited to these embodiments. The reagents, methods and equipment used in the present application, unless otherwise specified, are conventional reagents, methods and equipment in the art.
[0062] Example 1
[0063] Provided is a regenerated graphite, which is prepared using waste negative electrode as raw material according to a method comprising the following steps:
[0064] S1 secondary battery is discharged and disassembled to obtain waste negative electrode plates;
[0065] S2: the waste negative electrode sheet obtained by disassembling in step S1 is placed in a tube furnace, nitrogen is introduced, and the temperature is first increased to 400°C at a heating rate of 10°C / min, and then increased to 500°C at a heating rate of 4°C / min, and kept at this temperature for 1 hour to obtain a black powder;
[0066] S3: The black powder obtained in step S2 is placed in a muffle furnace, and the temperature is raised to 600°C at a rate of 5°C / min in an air atmosphere, and the temperature is kept for 1 hour for secondary calcination; after the heat preservation is completed, the calcined black powder is placed in a hydrochloric acid solution with a concentration of 0.1 mol / L at a ratio of 1g:0.0003mol hydrochloric acid, immersed at 70°C for 2h, and dried at 100°C to obtain acid-purified waste graphite;
[0067] S4: The waste graphite obtained in step S3 is put into a CVD tube furnace. After the tube furnace is heated to 1000°C at a heating rate of 10°C / min, gas is introduced into the CVD tube furnace at a volume ratio of acetylene:argon = 1:10, and the introduction flow rate is 100mL / min. The quartz special-shaped tube in the CVD tube furnace is kept rotating at 25r / min. After keeping warm for 40min, the acetylene gas is turned off to obtain regenerated graphite.
[0068] Example 2
[0069] Provided is a regenerated graphite, which is prepared using waste negative electrode as raw material according to a method comprising the following steps:
[0070] S1 secondary battery is discharged and disassembled to obtain waste negative electrode plates;
[0071] S2: the waste negative electrode sheet obtained by disassembling in step S1 is placed in a tube furnace, nitrogen is introduced, and the temperature is first increased to 400°C at a heating rate of 5°C / min, and then increased to 500°C at a heating rate of 1°C / min, and kept at this temperature for 1 hour to obtain a black powder;
[0072] S3: The black powder obtained in step S2 is placed in a muffle furnace, and the temperature is raised to 600°C at a rate of 5°C / min in an air atmosphere, and the temperature is kept for 1 hour; after the heat preservation is completed, the calcined black powder is placed in a hydrochloric acid solution with a concentration of 0.1 mol / L at a ratio of 1g:0.0003mol hydrochloric acid, immersed at 70°C for 2 hours, and dried at 100°C to obtain acid-purified waste graphite;
[0073] S4: The waste graphite obtained in step S3 is put into a CVD tube furnace. After the tube furnace is heated to 1000°C at a heating rate of 10°C / min, gas is introduced into the CVD tube furnace at a volume ratio of acetylene:argon = 1:10, and the introduction flow rate is 100mL / min. The quartz special-shaped tube in the CVD tube furnace is kept rotating at 25r / min. After keeping warm for 40min, the acetylene gas is turned off to obtain regenerated graphite.
[0074] Example 3
[0075] Provided is a regenerated graphite, which is prepared using waste negative electrode as raw material according to a method comprising the following steps:
[0076] S1 secondary battery is discharged and disassembled to obtain waste negative electrode plates;
[0077] S2: The waste negative electrode sheet obtained by disassembling in step S1 is placed in a tubular furnace, nitrogen is introduced, and the temperature is first increased to 350°C at a heating rate of 10°C / min, and then increased to 500°C at a heating rate of 4°C / min, and kept at this temperature for 1 hour to obtain a black powder;
[0078] S3: The black powder obtained in step S2 is placed in a muffle furnace, and the temperature is raised to 600°C at a rate of 5°C / min in an air atmosphere, and the temperature is kept for 1 hour; after the heat preservation is completed, the calcined black powder is placed in a hydrochloric acid solution with a concentration of 0.1 mol / L at a ratio of 1g:0.0003mol hydrochloric acid, immersed at 70°C for 2 hours, and dried at 100°C to obtain acid-purified waste graphite;
[0079] S4: The waste graphite obtained in step S3 is put into a CVD tube furnace. After the tube furnace is heated to 1000°C at a heating rate of 10°C / min, gas is introduced into the CVD tube furnace at a volume ratio of acetylene:argon = 1:10, and the introduction flow rate is 100mL / min. The quartz special-shaped tube in the CVD tube furnace is kept rotating at 25r / min. After keeping warm for 40min, the acetylene gas is turned off to obtain regenerated graphite.
[0080] Example 4
[0081] Provided is a regenerated graphite, which is prepared using waste negative electrode as raw material according to a method comprising the following steps:
[0082] S1 secondary battery is discharged and disassembled to obtain waste negative electrode plates;
[0083] S2: the waste negative electrode sheet obtained by disassembling in step S1 is placed in a tube furnace, nitrogen is introduced, and the temperature is first increased to 400°C at a heating rate of 5°C / min, and then increased to 500°C at a heating rate of 4°C / min, and kept at this temperature for 1 hour to obtain a black powder;
[0084] S3: The black powder obtained in step S2 is placed in a muffle furnace, and the temperature is raised to 600°C at a rate of 5°C / min in an air atmosphere, and the temperature is kept for 1 hour; after the heat preservation is completed, the calcined black powder is placed in a hydrochloric acid solution with a concentration of 0.1 mol / L at a ratio of 1g:0.0003mol hydrochloric acid, immersed at 70°C for 2 hours, and dried at 100°C to obtain acid-purified waste graphite;
[0085] S4: The waste graphite obtained in step S3 is put into a CVD tube furnace. After the tube furnace is heated to 1000°C at a heating rate of 10°C / min, gas is introduced into the CVD tube furnace at a volume ratio of acetylene:argon = 1:10, and the introduction flow rate is 100mL / min. The quartz special-shaped tube in the CVD tube furnace is kept rotating at 25r / min. After keeping warm for 40min, the acetylene gas is turned off to obtain regenerated graphite.
[0086] Example 5
[0087] Provided is a regenerated graphite, which is prepared using a waste negative electrode as a raw material and the method of Example 1. The difference from Example 1 is that in step S2, the process of primary calcination is: uniformly heating the temperature to 500°C at a heating rate of 10°C / min.
[0088] Example 6
[0089] Provided is a regenerated graphite, which is prepared using a waste negative electrode as a raw material and the method of Example 1. The difference from Example 1 is that in step S3, the secondary calcination process is: heating to 600°C at a rate of 10°C / min and keeping warm for 1 hour.
[0090] Example 7
[0091] Provided is a regenerated graphite, which is prepared using waste negative electrodes as raw materials and the method of Example 1. The difference from Example 1 is that in step S3, the secondary calcination process is: heating to 700°C at a rate of 5°C / min and keeping warm for 0.5h.
[0092] Example 8
[0093] Provided is a regenerated graphite, which is prepared using a waste negative electrode as a raw material and the method of Example 1. The difference from Example 1 is that in step S3, the specific process of acid leaching is: placing the calcined black powder in a hydrochloric acid solution with a concentration of 0.5 mol / L and immersing it at 40°C for 3 hours.
[0094] Example 9
[0095] Provided is a regenerated graphite, which is prepared using a waste negative electrode as a raw material and the method of Example 1. The difference from Example 1 is that in step S3, the specific process of acid leaching is: placing the calcined black powder in a hydrochloric acid solution with a concentration of 0.5 mol / L and immersing it at 80°C for 1 hour.
[0096] Comparative Example 1
[0097] This comparative example provides a regenerated graphite, which is prepared by using waste negative electrode as raw material and referring to the method of Example 1. The difference from Example 1 is that step S3 and subsequent operations are not performed.
[0098] Comparative Example 2
[0099] This comparative example provides a regenerated graphite, which is prepared by using waste negative electrode as raw material and referring to the method of Example 1. The difference from Example 1 is that in step S3, no secondary calcination is performed, and the black powder obtained in step S2 is directly placed in a 1 mol / L hydrochloric acid solution, immersed at 80°C for 3 hours, and the subsequent operations are performed.
[0100] Comparative Example 3
[0101] This comparative example provides a regenerated graphite, which is prepared by using waste negative electrode as raw material and referring to the method of Example 1. The difference from Example 1 is that in step S3, the atmosphere of the secondary calcination is a nitrogen atmosphere.
[0102] Comparative Example 4
[0103] This comparative example provides a regenerated graphite, which is prepared using waste negative electrodes as raw materials and referring to the method of Example 1. The difference from Example 1 is that in step S2, nitrogen is replaced by air, and in step S3, air is replaced by nitrogen.
[0104] The structural parameters of the regenerated graphite prepared in the above embodiments and comparative examples are shown in Table 1. In Table 1, the relevant parameters are obtained by conventional means in the art. Id represents the intensity of the D peak of the regenerated graphite in the Raman spectrum, and Ig represents the intensity of the G peak of the regenerated graphite in the Raman spectrum.
[0105] Table 1
[0106]
[0107] The regenerated graphite prepared in the above examples and comparative examples was used as negative electrode active material to prepare secondary batteries, and then the kinetic performance of the secondary batteries was tested.
[0108] The preparation of the secondary battery includes the following steps:
[0109] Positive electrode preparation
[0110] The positive electrode active material (NCM622), the conductive agent acetylene black and the binder polyvinylidene fluoride (PVDF) were mixed uniformly according to the mass ratio of "positive electrode active material: acetylene black: PVDF" = 94:3:3, and uniformly dispersed in 1-methyl-2-pyrrolidone (NMP) to prepare a uniform black slurry. The mixed black slurry was coated on both sides of the aluminum foil, baked, rolled and cut into pieces to obtain a compacted density of 0.33 g / cm 3 The positive electrode.
[0111] Preparation of negative electrode
[0112] The regenerated graphite prepared in the above embodiment and the comparative example was used as the negative electrode active material, the negative electrode active material, the conductive agent carbon nanotubes, the thickener carboxymethyl cellulose (CMC), and the binder styrene butadiene rubber (SBR) were mixed in a mass ratio of 94.3:1.5:1.2:3, and the solvent deionized water was added, and the mixture was stirred in a stirrer until the system was uniform to obtain a negative electrode slurry. The negative electrode slurry was evenly coated on the negative electrode current collector copper foil, placed in an oven for drying, and rolled and cut to obtain a negative electrode sheet (the compaction density of the sheet was 1.60 g / cm 3 ).
[0113] Electrolyte preparation
[0114] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain a mixed organic solvent, and then LiPF6 is dissolved in the mixed organic solvent. After mixing evenly, an electrolyte with a lithium ion concentration of 1 mol / L is obtained.
[0115] Secondary half-cell assembly
[0116] The button battery model is selected as CR2032, and the prepared negative electrode plate and separator (polypropylene, 16 μm) are cut into discs with diameters of 12 mm and 19 mm respectively. A lithium sheet with a diameter of 15.6 mm is selected, and the negative electrode bottom cover-gasket-negative electrode disc-diaphragm (with electrolyte)-lithium sheet-nickel mesh-positive electrode shell are assembled in sequence to obtain a secondary half-battery;
[0117] Assembly of secondary full battery
[0118] The prepared positive electrode sheet, separator (polypropylene, 16μm), and negative electrode sheet are stacked in order so that the separator is between the positive and negative electrode sheets, then wound into a battery cell and loaded into a soft-pack shell. After top and side sealing, liquid injection (electrolyte), formation, sorting and other processes, a lithium-ion secondary full battery is obtained.
[0119] The performance test of the secondary half-cell is as follows:
[0120] (1) AC impedance test:
[0121] Reference standard: WI-SUN7-17.25.1113-A1 "Full battery (high output) AC impedance test work guide";
[0122] Test parameters: disturbance voltage: 5mV, frequency range: 100kHz-100mHz;
[0123] (2) Specific capacity (mAh / g):
[0124] Reference standard: Negative electrode material: GB T-24533-2019 "Graphite negative electrode materials for lithium-ion batteries";
[0125] Equipment: Blue Electric 5V-5mA test cabinet;
[0126] Test process: At room temperature (25±5℃), the button half-cell is discharged to 5mV at 0.05C, left standing for 5 minutes, discharged to 5mV at 0.05mA, left standing for 5 minutes, discharged to 5mV at 0.01mA, and the first discharge capacity Cap1 is obtained; left standing for 5 minutes, charged to 2V at 0.1C, and the first charge capacity Cap2 is obtained;
[0127] (3) First coulombic efficiency (%):
[0128] Same as the above specific capacity test, the first coulombic efficiency is the ratio of Cap2 / Cap1;
[0129] The performance test of the secondary full battery is as follows:
[0130] (4) Rate performance (2C charge capacity retention rate compared to 0.1C at 25°C):
[0131] At room temperature (25±5℃), the secondary full battery is charged to 3.65V at 0.1C constant current and constant voltage, the cut-off current is 0.05C, and then discharged to 2.5V at 0.1C constant current. The room temperature discharge capacity is recorded as Cap1; at room temperature, the secondary full battery is charged to 3.65V at 2.0C constant current and constant voltage, the cut-off current is 0.05C, and then discharged to 2.5V at 0.1C constant current. The room temperature discharge capacity is recorded as Cap2; the rate performance is the ratio of Cap2 / Cap1;
[0132] (5) Cycle stability: The secondary battery was placed in an environment of 45±3°C, charged at 1C constant current and constant voltage to 3.65V, with a cut-off current of 0.05C, and discharged at 1C constant current to 2.5V. This charge and discharge step was recorded as one cycle. This cycle was repeated and the capacity retention rate after 100 cycles was recorded.
[0133] The test results are shown in Table 2.
[0134] Table 2
[0135]
[0136] From the above results, we can see that:
[0137] The regenerated graphite recovered and prepared by the method of the present invention has low impurity content and high graphitization degree, and the battery prepared by using the regenerated graphite has good comprehensive electrochemical performance.
[0138] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A method for recovering graphite from waste negative electrodes, characterized in that: The following steps are involved: S1 secondary battery is discharged and disassembled to obtain waste negative electrode plates; S2: the waste negative electrode sheet obtained by disassembling in step S1 is placed in an inert atmosphere for calcination to obtain a black powder; S3: the black powder obtained in step S2 is placed in an air atmosphere for secondary calcination, and then subjected to acid leaching, washing and drying to obtain waste graphite; S4: The waste graphite obtained in step S3 is calcined under the conditions of a carbon source and an inert atmosphere, and a carbon layer is vapor-deposited on the surface of the waste graphite to obtain regenerated graphite.
2. The method for recovering graphite from waste negative electrodes according to claim 1, characterized in that: The primary calcination in step S2 is carried out at a temperature of 300-500° C. and for a time of 0.5-3 h.
3. The method for recovering graphite from waste negative electrodes according to claim 2, characterized in that: The calcination procedure of the primary calcination in step S2 is: firstly heating the temperature to 350-400°C at a heating rate of 5-10°C / min, and then heating the temperature to 500°C at a heating rate of 1-4°C / min.
4. The method for recovering graphite from waste negative electrodes according to claim 1, characterized in that: The secondary calcination in step S3 is carried out at a temperature of 500-700° C., for a time of 0.5-1 h, and at a heating rate of 5-10° C. / min.
5. The method for recovering graphite from waste negative electrodes according to claim 1, characterized in that: The acid leaching conditions in step S3 satisfy at least one of the following characteristics: (1) The acid used for pickling includes at least one of hydrochloric acid, nitric acid, sulfuric acid, citric acid, boric acid, acetic acid, acetic acid, gluconic acid, and oxalic acid; (2) During the acid leaching process, the ratio of black powder to acid is 1g: 0.0003-0.005mol; (3) The acid concentration in the acid solution used for acid leaching is 0.1-0.5 mol / L; (4) The acid leaching temperature is 40-80°C and the immersion time is 1-3h.
6. The method for recovering graphite from waste negative electrodes according to claim 1, characterized in that: The vapor deposition in step S4 satisfies at least one of the following conditions: (1) The carbon source includes at least one of acetylene, methane, ethylene, propane, toluene, cyclohexane, ethanol, ethylene, propylene, pyrrole, and acetonitrile; (2) The carbon source is introduced at a flow rate of 10-400 mL / min; (3) The calcination temperature is 800-1200°C, the time is 10-60min, and the heating rate is 5-10°C / min.
7. The method for recovering graphite from waste negative electrodes according to claim 1, characterized in that: The gas forming the inert atmosphere includes at least one of helium, argon and nitrogen.
8. A graphite negative electrode material, characterized in that: The graphite negative electrode material is prepared by the method for recovering graphite from waste negative electrodes according to any one of claims 1 to 7.
9. A secondary battery comprising a positive electrode sheet, an electrolyte, a separator and a negative electrode sheet, characterized in that: The negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the graphite negative electrode material as claimed in claim 8.
10. An electrical device, characterized in that: The electric device comprises the secondary battery according to claim 9.
Citation Information
Cited By
Method for recycling ternary lithium battery based on front impurity removal
CN120637652A
Waste graphite regeneration method, regenerated graphite negative electrode material and secondary battery
CN120987314A